Surgical treatment of advanced cervical cancer - Esteves Flores, Luis (2015)
The author reviews the actual criteria for the treatment of the advanced carcinoma of the cervix, he presents his experience of 55 cases treated with pelvic exenteration at the instituto Nacional de Enfermedades Neoplásicas, Lima Perú , between 1953 and 1965. The overall survival rate in his serie was 11 %; several tables with morbidity and mortality data are presented. The author remarks the circumstances and procedures useful for the opportune radical treatment of the advanced carcinoma of the cervix.